Cross-border cooperation in the energy sector - Frank Baur; Barbara Dröschel (Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation, 2022)
The recent history of the Greater Region has been strongly characterised by fossil fuels. The area thus faces significant challenges as a model region in terms of the cross-border activities necessary to meet the requirements of climate protection and the energy transition. Based on the targets defined in Europe, this paper presents examples of approaches to action and projects undertaken in the field of energy in the Greater Region. Experiences gathered in the area - including those of the authors - reveal the need for action, firstly in relation to the implementation of structures and networks, and secondly to the potential development of research excellence in the field of energy/climate protection. As relevant actors in the energy transition, the municipalities have a particular role to play here.
urn:nbn:de:0156-40971282; hdl:10419/258994; https://econpapers.repec.org/RePEc:zbw:arlabe:33
Keywords: 710; Energy transition; climate protection; cross-border energy projects; network structures; zero-emissions municipalities; research platform